Impact of Sources of Damping On the Fragility Estimates of Wind Turbine Towers - Fitzgerald, Breiffni (My University, 2024)
Fragility estimates in wind turbine towers have been investigated but the the effect of damping on fragility has not been studied. While damping can often be small, it can come from different sources for a wind turbine. This paper demonstrates that even for small levels of equivalent viscous damping, a combination of sources can have a significant impact on the estimate of the fragility of a wind turbine in operational conditions. The widely studied 5MW reference wind turbine is considered for this study. The fragility analysis is performed considering the tower fore-aft displacement and acceleration responses. The impact of different sources of damping on fragility is estimated and ranked to qualitatively understand the impact of damping on the lifetime performance of the tower and develop approximate estimates of their quantitative changes.
PUBLISHED
Keywords: Smart & Sustainable Planet; Reliability (Engineering); Renewable energies; Renewable energy; Structural Dynamics; Structural Engineering; Wind Energy and Wind Turbines